Considerations about the sociocultural and environmental landscape of the Jaú River - Lyra, Anna Maria Galvão Carneiro; Constantino, Norma Regina Truppel (National Journal of City Management, 2024)
Despite fundamental roles of rivers in the history and evolution of urban centers, city design has often disregarded water networks in the midst of accelerated urban expansion. The lack of connection between rivers and the urban landscape has over time contributed to the exacerbation of socio-environmental problems. This research aims at understanding the relationship between the Jaú River and Jaú’s cityscape through the following perspectives proposed by Jean-Marc Besse (2014): historical, sociocultural and socio-environmental landscapes. The river landscape of Jaú is characterized based on information taken from scientific and documentary sources (textual, iconographic and cartographic). The results of analysis are then presented to systematically characterize challenges to landscape planning in this case study. This research pertains to the contemporary effort aiming at understanding landscapes by analyzing historical and current perspectives allowing us to restore connections between a city and its natural environment. In conclusion, it is argued that the neglect of the Jaú River valley throughout urban expansion contributed to the disconnection between the river landscape, the city and its inhabitants’ daily lives. As an alternative, we propose a landscape planning process that integrates the river’s environmental and social dimensions.